Ethiopia: the urban food-for-work project - International Food Policy Research Institute (International Food Policy Research Institute, 2002)
IFPRI assessed CARE-Ethiopia's Urban Food-for-Work Project in order to draw lessons about how to work effectively in urban areas. This country study gives information on the research focus, under Project Leader, James Garrett, highlights of the research, and recommendations for further action.